Early antiretroviral therapy reduces hiv dna following perinatal HIV infection - Foster, C; Pace, M; Kaye, S; Hopkins, E; Jones, M; Robinson, N; Fidler, S; Frater, J; CHERUB Investigators (Lippincott, Williams & Wilkins, 2017)
: The impact of antiretroviral therapy (ART) on the size of the HIV reservoir has implications for virological remission in adults, but is not well characterised in perinatally acquired infection (PaHIV). In a prospective observational study of 20 children with PaHIV and sustained viral suppression on ART for >5 years, proviral DNA was significantly higher in deferred (>4 years) versus early (first year of life) ART recipients (p = 0.0062), and correlated with age of initiation (p = 0.13; r = 0.57). No difference was seen in cell-associated viral RNA (p = 0.36). Identifying paediatric populations with smaller reservoirs may inform strategies with potential to induce ART-free remission.